A 2‐O‐Methylriboside Unknown Outside the RNA World Contains Arsenic. (17th August 2017) - Glabonjat, Ronald A.; Raber, Georg; Jensen, Kenneth B.; Guttenberger, Nikolaus; Zangger, Klaus; Francesconi, Kevin A.
Abstract: Lipid‐soluble arsenic compounds, also called arsenolipids, are ubiquitous marine natural products of currently unknown origin and function. In our search for clues about the possible biological roles of these compounds, we investigated arsenic metabolism in the unicellular green alga Dunaliella tertiolecta, and discovered an arsenolipid fundamentally different from all those previously identified; namely, a phytyl 5‐dimethylarsinoyl‐2‐ O ‐methyl‐ribofuranoside. The discovery is of particular interest because 2‐ O ‐methylribosides have, until now, only been found in RNA. We briefly discuss the significance of the new lipid in biosynthesis and arsenic biogeochemical cycling.